HYDROLOGY OF THE VANCH RIVER THE TRIBUTARY OF THE TRANSBOUNDARY PYANJ RIVER UNDER CLIMATE CHANGE - Normatov Inom Sherovich; Goncharuk Vladislav Vladimirovich; Normatov Parviz Inomovich; Odinaev Qodir Nodirovich (Scientific Journal of Pedagogy and Economics, 2020)
For the period 1958-2018, the atmospheric precipitation in the Vanch river basin remained almost unchanged, due to the free penetration of wet masses of Mediterranean and Caucasian cyclones and the relatively weak influence of orography of the mountainous area. The average annual temperature of the considered period is characterized by weak increases of 3·10-3 о С/year. The effect of climate change on river runoff was determined by comparing their values in the two periods 1940-1970 and 1986-2016, which showed a significant increase for the period 1986-2018. The Vanch river hydrograph in the corresponding periods showed the shift of maximum runoff value to the left, which indicates an early period of melting of the snow cover and glaciers on the river upstream.